MODEL PEMBELAJARAN EKSPERIENSIAL JELAJAH ALAM SEKITAR. STRATEGI UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MAHASISWA - Siti Alimah (Universitas Negeri Semarang, 2014)
This study aims to analyze whether the model of Experiential Jelajah Alam Sekitar* in the biological learning process can improve students’ critical thinking skills. The method used in this study was a Quasi Experiment with design nonequivalent control group design and the design model of pretest- posttest control group design. The results showed that the application of the Experiential Nature Roaming Around in biology learning can enhance students’ critical thinking skills.